Transforming Classroom Learning with Augmented Reality: Pedagogical Implications for Integrating AR into Language Learning Curriculum - Azhariah Rachman; Sahra Osman; Ana Durrotul Hikmah (Yayasan Adra Karima Hubbi, 2026)
Background. Augmented Reality (AR) has emerged as a powerful tool in transforming traditional classroom learning by offering immersive and interactive learning experiences. In language education, AR can bridge the gap between theoretical knowledge and real-world application, enhancing engagement and comprehension. However, the pedagogical implications of integrating AR into language learning curricula remain underexplored, particularly in terms of how AR can influence student motivation, participation, and language proficiency. Purpose. This study aims to investigate the pedagogical implications of integrating AR into language learning curricula. The research explores how AR-based learning environments impact student engagement, language skills development, and overall learning outcomes in language classrooms. Method. A mixed-methods approach was adopted, including pre- and post-assessments of language proficiency, engagement surveys, and interviews with students and instructors. The study was conducted in language classrooms where AR tools were integrated into lesson plans over a 12-week period. Results. Findings indicate that the use of AR in language learning significantly increased student engagement and motivation, with notable improvements in vocabulary retention, speaking, and listening skills. Students reported higher levels of enjoyment and felt more confident in using the language in practical contexts. Conclusion. AR can enhance language learning by offering interactive, context-rich experiences that support both linguistic and cognitive development. This research highlights the potential of AR to transform language education, making learning more engaging and effective.